2018
DOI: 10.3892/ijo.2018.4422
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TIMP-1 in PECAM-1-mediated tumor dissemination

Abstract: Platelet endothelial cell adhesion molecule-1 (PECAM-1) is expressed on the vascular endothelium and has been implicated in the late progression of metastatic tumors. The activity of PECAM-1 appears to be mediated by modulation of the tumor microenvironment (TME) and promotion of tumor cell proliferation, rather than through the stimulation of tumor angiogenesis. The present study aimed to extend those initial findings by indicating that the presence of functional PECAM-1 on the endothelium promotes a prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 82 publications
0
30
0
3
Order By: Relevance
“…Among the top 10 genes with a high average Δ PCC in lung adenocarcinoma (LUAD), several genes such as CLDN18, ADAMTS8, PECAM1 and SFTPA1 have been known to be associated with LUAD in previous studies [ 31 33 ]. No direct relation of NSUN2 and SLC39A8 with lung squamous cell carcinoma (LUSC) has been known so far.…”
Section: Discussionmentioning
confidence: 99%
“…Among the top 10 genes with a high average Δ PCC in lung adenocarcinoma (LUAD), several genes such as CLDN18, ADAMTS8, PECAM1 and SFTPA1 have been known to be associated with LUAD in previous studies [ 31 33 ]. No direct relation of NSUN2 and SLC39A8 with lung squamous cell carcinoma (LUSC) has been known so far.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had reported that CDH5 expression is associated with multiple tumors [ 43 , 44 ], such as gastric cancer and breast cancer, but the relationship between CDH5 and LUAD is still to be determined. PECAM1 is a multifunctional cell adhesion molecule involved in numerous physiologic processes within the vasculature; Abraham et al found that the activity of PECAM1 appears to be associated with the tumor microenvironment and tumor cell proliferation [ 45 ]; Kuang et al demonstrated that PECAM1 could be a potential prognostic factor and therapeutic target in NSCLC [ 46 ]. The von Willebrand factor (VWF) is a multimeric glycoprotein and plays an essential role in mediating platelet-tumor cell interactions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinic trails have mentioned a worn that metformin could reduce the platelets which affluent express PECAM-1 on its surface. Herein, we put forward a hypothesis, and metformin could involve in PECAM-1 regulation, which can further affect cisplatin resistance for irradiated cells [19].…”
Section: Ivyspringmentioning
confidence: 99%